The effect of four-week high-intensity interval training with beta-alanine supplementation on aerobic and anaerobic performance and some blood parameters in girls basketball players - bahareh ketabdar; mehrdad fathie (Journal of Advanced Biomedical Sciences, 2017)
Background & Objective: The aim of the present study was to determine the effect of four-week high-intensity interval training with beta-alanine supplementation on aerobic and anaerobic performance and some blood parameters in girls basketball players.